YESUS SAHABAT DI PERJALANAN: REFLEKSI PANDEMI COVID-19 DARI SUDUT PANDANG IMAN KRISTIANI - Tonius Hia (Diegesis : Jurnal Teologi, 2022)
Suffering is a reality that is experienced by each person as an integral part of their life. The experience of suffering is inevitable. At this moment, the experience of suffering by some people is exposed by a coronavirus (Covid-19). The virus is able to spread so quickly, that it can threaten the lives of everyone exposed. This pandemic phenomenon has resulted in a crisis in society, especially in social and economic life. Besides that, the crisis is happening too in people’s faith. There are so many people who are despairing and hopeless because they must accept the fact that one of their family members was exposed to a virus and died. However, this situation must be responded to by the Christian faith, so that there is no despair and hopelessness. Through the Christian faith, the Christians do not avoid suffering but face it because in this suffering people get salvation.